A cloud GIS-based framework implementation in developing countries - Wawan Hendriawan Nur; Ida Narulita; Yugo Kumoro; Yuliana Susilowati; Yuliana Yuliana; Faiz Rohman Fajary; Sekar Nur Wulandari (Bulletin of Electrical Engineering and Informatics, 2022)
Cloud computing technology has successful cost savings, business effectiveness, and higher scalability in various fields, including the government field. The pandemic Covid-19 era has been accelerating the adoption of cloud technology; the enterprises have instructed the employees to work from home to reduce transmission. The cloud-based framework for government in developing countries was developed. However, it was arduous to apply in Indonesia as a developing country, especially in areas where technology infrastructure, human resources, and funding are insufficient. Thus, the study of the cloud implementation framework in developing countries is essential. This paper used the enterprise architecture planning method for designing a cloud GIS-based framework. The developed framework successfully implemented the cloud-based GIS technology in Indonesia with limited ownership and infrastructure of technology, resources, and funding.